Aportación al conocimiento de Ranunculus peltatus Schrank subsp. saniculifolius (Viv.) C.D.K.Cook, y su comportamiento fitosociológico. - Velayos Rodríguez, Mauricio; Pascual, Pilar; Cirujano, Santos (Botanica Complutensis, 1986)
Sin resumen